The crisis of democracy and the rule of law in some new Member States of the European Union - Di Gregorio, Angela (Journal of the Belarusian State University. Law, 2019)
The paper analyses one of the hot topics of the constitutional debate in Europe, that is democratic backslidings in some new EU Members States. Although many works in the international literature have been devoted to this subject, a general analysis of the political and constitutional causes of this regression is lacking. It is therefore necessary to analyze the characteristics of the transition to democracy; the EU “rule of law ” mechanisms and their failure, including the failure of the system of democratic conditionality; the cultural and constitutional framework of the new EU Member States, including some defects in their constitutional engineering.
Keywords: rule of law; European conditionality; constitutional engineering; constitutional courts